Le nom "catégorie", au croisement de la généralité et de la sous-spécification - Marie Lammert (Corela)
In this paper, we question the linguistic status of the French noun catégorie. By its semantic properties, catégorie can be considered as a general or sommital noun, while it can be apprehended as a subspecified noun or signalling noun if syntactic criteria are taken into account. We first show that catégorie is a general noun because of its lexical position, its referential non-autonomy, its intrinsic underdetermination and its abstraction. We also highlight the nature of the link between N2 and catégorie in the Dét catégorie de Dét N2 structure, as well as the semantic nature of it. The semantic properties of catégorie are then related to its syntactic characteristics. The latter do not allow concluding an affiliation to the class of the subspecified nouns, except at the edge of it.